INNOVATIVE FISH DRIED TECHNOLOGIES - Lebskaya Tatyana Konstantinovna; Borisenko Ruslana Vasilievna; Bondarenko Evgeia Vitalievna (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper makes analyses of the Innovative technologies of fish products. On this case, drying, which is associated with the use of air ions, which are widely used in numerous sectors of the national economy was discovered. Hence, it has concluded that ionized air exhibits a bactericidal and preservative effect, which contributes to the production of good quality products and ensures its safety for long-term storage